Schedulability Analysis of Sporadic Messages in the FlexRay Dynamic Segment - Lange, Rodrigo; Oliveira, Rômulo S. de; Bonet, Eduardo; Vasques, Francisco (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2012)
FlexRay is a communication protocol heavily promoted as the future de facto standard for automotive systems. A major challenge associated with the design of FlexRay systems is the response time analysis of sporadic messages transmitted in the dynamic segment, a problem that has been shown to be a combinatorial problem. Although there are several methods available to make this analysis, they mainly rely on optimization techniques such as Integer Linear Programming (ILP), or use the Real-Time Calculus (RTC) framework. In this work we propose a method with pseudo-polynomial complexity to derive an upper bound for sporadic messages transmitted in the dynamic segment. We assess the performance of the proposed method comparing it with state-of-the-art methods available in the literature.